Investigation of cellular and molecular mechanisms of caffeic acid phenethyl ester loaded nanoparticle systems in breast cancer cell lines - Poyraz, Fatma Sayan; Colpan, Reyhan Dilsu; Derman, Serap; Mansuroglu, Banu; Erdemir, Aysegul (ELSEVIER SCI LTD, 2023)
Breast cancer is associated with high morbidity and mortality in women since conventional treatment methods are limited due to toxicity problems and inadequate targeting of cancer cells. The aim of this study is to develop caffeic acid phenethyl ester (CAPE) loaded polymeric nanoparticles to provide treatment for breast cancer and investigate their anti-tumor activity on MCF-7 and MDA-MB-231 breast cancer cells. CAPE was encapsulated into poly lactic-co-glycolic acid (PLGA) polymer using single-emulsion (o/w) solvent evaporation method and characterization of CAPE loaded PLGA nanoparticles (CAPE-NPs) were performed by particle size, zeta potential, polydispersity index, in vitro release profile, and surface morphology. CAPE-NPs were tested for cytotoxicity, anti-migration, anti-proliferation and apoptotic activities on breast cancer cells. The mean nanoparticle size was found as 196,1 +/- 8982 nm and polydispersity index (PDI) was 0186 +/- 0069. The results of the in vitro cell culture studies indicated that treatment of breast cancer cells with CAPE and CAPE-NPs inhibited cell viability and proliferation. IC50 values for 48 h were determined as 28.35 mu g/ml,19.57 mu g/ml for CAPE and CAPE-NP, respectively. Additionally, CAPE-NPs induced intrinsic pathway of apoptosis in MCF-7 and MDA-MB-231 cell lines. Overall, CAPE-NPs showed more efficient anti-tumour activity on breast cancer cells by small size and enhanced bioavability.
Keywords: CAPE; Polymeric nanoparticle; Breast cancer; Anti-tumor activity; ANTICANCER ACTIVITY; APOPTOSIS; CURCUMIN; EXPRESSION; PATHWAYS; PCR; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Engineering